The Role of Environmental Conditions and Purchasing Power Parity in Determining Quality of Life among Big Asian Cities - Audi, Marc; Ali, Amjad (International Journal of Energy Economics and Policy, 2023)
This article has examined the role of environmental conditions and purchasing power parity in deciding the quality of life among big Asian cities. The study has constructed an index for quality of life with the help of housing, crime rates, death rate, average life expectancy, environmental degradation, and level of education. Quality of life has been selected as the dependent variable and the level of pollution, availability of health care facilities, local purchasing power, availability of groceries, level of democracy, cost of living, restaurants, level of traffic, and level of rents are selected explanatory variables. For empirical analysis, this study uses data for the years 2017, 2018, and 2019. The estimated results show that pollution has a negative and significant impact on the quality of life in the case of Asian cities. Local purchasing power has a positive and significant relationship with the quality of life in the cities of Asia. Groceries and democracy are very important parts of the daily life of human beings but they have insignificant impacts on the quality of life in Asian cities. Restaurants have a positive and significant impact on quality of life. This study finds that level of traffic and the level of rent have a negative and significant impact on the quality of life in the case of Asian cities. The overall results conclude that selected indicators play a significant role in determining the quality of life in Asian cities.